Graves' disease and radioiodine therapy - Kobe, C.; Weber, I.; Eschner, W.; Sudbrock, F.; Schmidt, M.; Dietlein, M.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2008)
Aim: This study was performed to analyse the impact of the choice of antithyroid drugs (ATD) on the outcome of ablative radioiodine therapy (RIT) in patients with Graves' disease. Patients, material, methods: A total of 571 consecutive patients were observed for 12 months after RIT between July 2001 and June 2004. Inclusion criteria were the confirmed diagnosis of Graves' disease, compensation of hyperthyroidism and withdrawal of ATD two days before preliminary radioiodine-testing and RIT. The intended dose of 250 Gy was calculated from the results of the radioiodine test and the therapeutically achieved dose was measured by serial uptake measurements. The end-point measure was thyroid function 12 months after RIT; success was defined as elimination of hyperthyroidism. The pretreatment ATD was retrospectively correlated with the results achieved. Results: Relief from hyperthyroidism was achieved in 96 % of patients. 472 patients were treated with carbimazole or methimazole (CMI) and 61 with propylthiouracil (PTU). 38 patients had no thyrostatic drugs (ND) prior to RIT. The success rate was equal in all groups (CMI 451/472; PTU 61/61; ND 37/38; p=0.22). Conclusion: Thyrostatic treatment with PTU achieves excellent results in ablative RIT, using an accurate dosimetric approach with an achieved post-therapeutic dose of more than 200 Gy.
Keywords: Radioiodine therapy; Graves' disease; antithyroid drugs; thyrostatic medication; hyperthyroidism; dosimetry